Epidemiology and risk factors of extensively drug-resistant Pseudomonas aeruginosa infections - Nattawan Palavutitotai (2019)
© 2018 Palavutitotai et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited. Background The incidence of nosocomial infections from extensively drug-resistant Pseudomonas aeruginosa (XDR-PA) has been increasing worldwide. We investigated the prevalence and factors associated with XDR-PA infections, including the factors that predict mortality. Methods We retrospectively studied a cohort of adult, hospitalized patients with P. aeruginosa (PA) infections between April and December 2014. Results Of the 255 patients with PA infections, 56 (22%) were due to XDR-PA, 32 (12.5%) to multidrug resistant Pseudomonas aeruginosa (MDR-PA), and 167 (65.5%) to non-MDR PA. Receiving total parenteral nutrition (adjusted OR [aOR] 6.21; 95% CI 1.05–36.70), prior carbapenem use (aOR 4.88; 95% CI 2.36–10.08), and prior fluoroquinolone use (aOR 3.38; 95% CI 1.44–7.97) were independently associated with the XDR-PA infections. All XDR-PA remained susceptible to colistin. Factors associated with mortality attributable to the infections were the presence of sepsis/septic shock (aOR 11.60; 95% CI 4.66–28.82), admission to a medical department (aOR 4.67; 95% CI 1.81–12.06), receiving a central venous catheter (aOR 3.78; 95% CI 1.50–9.57), and XDR-PA infection (aOR 2.73; 95% CI 1.05–7.08). Conclusion The prevalence of XDR-PA infections represented almost a quarter of Pseudomonas aeruginosa hospital-acquired infections and rendered a higher mortality. The prompt administration of an appropriate empirical antibiotic should be considered when an XDR-PA infection is suspected.